DISFEMISME BAHASA KLUET DALAM TUTURAN MASYARAKAT DI KABUPATEN ACEH SELATAN - Mairoja, Fera; Iskandar, Denni; Iqbal, Muhammad; Fauzi, Mohd. (Universitas Lancang Kuning, 2024)
This research intends to (1) explain the form of Kluet language dysphemism, (2) analyze the context of the use of Kluet language dysphemism, and (3) explain the function of Kluet language dysphemism in the speech of the people of South Aceh Regency. This study used a descriptive qualitative method. The researchers took four informants from each sub-district who were used as data sources, namely North Kluet, South Kluet, East Kluet, and Central Kluet Districts. The findings of this research indicate that the form of Kluet language dysphemism contains three forms; the form of words, phrases, and clauses, then context of the use of Kluet language dysphemism consists of the context of habit, anger, talkative/surprised, and prohibiting. Furthermore, the function of using Kluet's dysphemism contains five functions, namely functions to insult, threaten, hurt/annoy, as a joke, and express strong, heavy, and extreme emotions. Conversely, as regards the findings of research and data analysis, the primary forms of dysphemism are phrases and the main context of dysphemism is anger and habit.